2013
DOI: 10.1017/s1751731113001584
|View full text |Cite
|
Sign up to set email alerts
|

Passage kinetics of concentrates in dairy cows measured with carbon stable isotopes

Abstract: Fractional passage rates form a fundamental element within modern feed evaluation systems for ruminants, but knowledge on feed-specific fractional passage is largely lacking. Commonly applied tracer techniques based on externally applied markers, such as chromium-mordanted neutral detergent fibre (Cr-NDF), have been criticised for behaving differently to feed particles. This study describes the use of the carbon stable isotope ratio ( 13 C : 12 C) as an internal digesta marker to quantify the fractional passag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
6
7
0
Order By: Relevance
“…Curve fit accuracy based on the MPE was in the range of previous studies using δ 13 Clabeled forage (Pellikaan et al, 2013;Warner et al, 2013a) but MPE values were almost double compared with those reported for δ 13 C-labeled concentrates pulse dosed at high amounts (9 kg; Warner et al, 2013b). Interestingly, curve fit accuracy for Cr-NDF based on fecal sampling was considerably better than that for stable isotopes, but accuracy considerably declined for Cr-NDF with omasal digesta sampling and was even slightly worse than that of δ 15 N. These findings suggest that the small ruminal pulse dose size of stable isotopes probably affected its curve fit accuracy, and that omasal sampling provided somewhat less reliable results than fecal sampling.…”
Section: Choice Of Marker and Sampling Site To Estimate Passage Kineticssupporting
confidence: 51%
See 1 more Smart Citation
“…Curve fit accuracy based on the MPE was in the range of previous studies using δ 13 Clabeled forage (Pellikaan et al, 2013;Warner et al, 2013a) but MPE values were almost double compared with those reported for δ 13 C-labeled concentrates pulse dosed at high amounts (9 kg; Warner et al, 2013b). Interestingly, curve fit accuracy for Cr-NDF based on fecal sampling was considerably better than that for stable isotopes, but accuracy considerably declined for Cr-NDF with omasal digesta sampling and was even slightly worse than that of δ 15 N. These findings suggest that the small ruminal pulse dose size of stable isotopes probably affected its curve fit accuracy, and that omasal sampling provided somewhat less reliable results than fecal sampling.…”
Section: Choice Of Marker and Sampling Site To Estimate Passage Kineticssupporting
confidence: 51%
“…Incubations (0,2,4,8,24,48, and 72 h) started with the 72-h incubation bags according to the all-out procedure at 80 h after marker administration to ensure similar conditions of degradation and passage rates. Previous studies showed that fecal marker concentrations were close to baseline concentrations after 4 d (Warner et al, 2013b). Fractional rumen degradation rates were related to fractional rumen passage rates to test a potential relationship.…”
Section: Sampling and Measurementsmentioning
confidence: 93%
“…The absence of an effect of R:C ratio on passage rates of concentrate (Poore et al, 1990;Warner et al, 2013) and roughage (Poore et al, 1990;Rotger et al, 2005) has been demonstrated before, as reviewed by Offer and Dixon (2000) for cattle. A negative effect of concentrate proportion on rumen volume, as observed in adult ruminants (Owens and Goetsch, 1986), was absent in our study.…”
Section: Passage Rates Of Concentrate and Strawmentioning
confidence: 77%
“…the C/C ratio) may be constant between the moment of marker administration and the time of collection in the undigested faecal matter. Recent studies have shown that microbial fermentation did not affect the C/C ratio in apparent undigested material in vitro and in vivo (Ferreira LMM, unpublished) and that the 13 C/ 12 C ratio remained constant over time. Hence digestion of the labelled nutrient did not alter the isotopic ratio and its FPR in those studies.…”
Section: Stable Isotopes As Digesta Passage Markersmentioning
confidence: 99%
“…However, data based on such markers are scarce. Isotopically labelled feed has been applied in early ruminant metabolic studies but was only recently applied in ruminant digestion studies or specifically to quantify passage kinetics . Here we provide an overview of recent digesta passage research and discuss opportunities and limitations of using the isotopic signature ( δ ) of dietary components as a potential novel marker to quantify FPR in ruminants.…”
Section: Introductionmentioning
confidence: 99%